2017
DOI: 10.1016/j.ijpara.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis induces pathogenic dysbiosis of human intestinal microbiota biofilms

Abstract: Giardia duodenalis is a prevalent cause of acute diarrheal disease worldwide. However, recent outbreaks in Italy and Norway have revealed a link between giardiasis and the subsequent development of chronic post-infectious irritable bowel syndrome. While the mechanisms underlying the causation of post-infectious irritable bowel syndrome remain obscure, recent findings suggest that alterations in gut microbiota communities are linked to the pathophysiology of irritable bowel syndrome. In the present study, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 78 publications
2
110
1
4
Order By: Relevance
“…Furthermore, additional surveys indicate increased levels of families belonging to Bacteroidetes phylum [27,53], Giardia duodenalis constituting one of the commonly related post-infections parasites in IBS, microbiota's biofilm indicating a reduction from 100-210 to 10-105 µM [54]. Lyra et al [29] designed a study with the aim of distinguishing IBS subtypes by dividing volunteers into three categories: IBS-D, IBS-C, and IBS-M.…”
Section: It Is a Bug Situationmentioning
confidence: 99%
“…Furthermore, additional surveys indicate increased levels of families belonging to Bacteroidetes phylum [27,53], Giardia duodenalis constituting one of the commonly related post-infections parasites in IBS, microbiota's biofilm indicating a reduction from 100-210 to 10-105 µM [54]. Lyra et al [29] designed a study with the aim of distinguishing IBS subtypes by dividing volunteers into three categories: IBS-D, IBS-C, and IBS-M.…”
Section: It Is a Bug Situationmentioning
confidence: 99%
“…Exposure of lab strains of Escherichia coli or human intestinal microbiota to Giardia was able to convert the bacteria to a toxic state that is deadly to Caenorhabditis elegans [27]. Moreover, the same group demonstrated that Giardia caused not only microbial dysbiosis in co-cultures with human mucosal microbial biofilms, but also increased virulence of commensal microbiota towards human epithelial cells in vitro ; this report also described increased levels of inflammatory markers in humanized germ-free mice that were reconstituted with human intestinal microbes that had been exposed to Giardia products, but not the living parasite [28]. These Giardia -altered biofilms were capable of inducing immunopathology (intestinal permeability) that was dependent on microbial community disruption caused by Giardia secretory proteases.…”
Section: Giardia Interactions With Intestinal Commensal Microbiotamentioning
confidence: 99%
“…Infection with certain pathogens is known to lead to microbiome dysbiosis (Beatty et al, 2017), which has been implicated in a variety of post-infectious inflammatory disorders in humans. Parasitic (e.g., Giardia duodenalis) and bacterial (e.g., Campylobacter jejuni) infections have been found to cause post-infectious irritable bowel syndrome and flares in patients with inflammatory bowel (Buret, 2016).…”
Section: Microbiome and Host-pathogen Interactionsmentioning
confidence: 99%